2017
DOI: 10.21614/chirurgia.112.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Management of Multifocal-Multicentric Breast Cancer: Current Perspective

Abstract: RezumatIncidenţa cancerului de sân multicentric (MC) şi multifocal (MF) are rezultate diverse printre diferitele studii clinice existente în prezent, în principal, din cauza lipsei unei clasificãri şi a unei definiţii standardizatea a acestor douã entitãţi diferite. Tratamentul chirurgical optim pentru cancerul de sân multiplu ipsilateral, rãmâne un subiect de discuţie. Chirurgia conservatoare a sânului are o contraindicaţie relativã în tratamentul cancerului multifocal şi al cancerul multicentric. În acest re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…For patients with localized BC, surgery is recommended. About 6% of patients with localized BC will finally develop metastatic disease and 10–40% have systemic relapse [ 6 ]. Chemotherapy, radiotherapy, and immunotherapy are recommended for the treatment of BC patients with metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with localized BC, surgery is recommended. About 6% of patients with localized BC will finally develop metastatic disease and 10–40% have systemic relapse [ 6 ]. Chemotherapy, radiotherapy, and immunotherapy are recommended for the treatment of BC patients with metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy, radiotherapy, and immunotherapy are recommended for the treatment of BC patients with metastatic disease. Although great progresses (including the discovery of novel therapeutic targets and the understanding of mechanisms of resistance to treatment) have been made for the management of patients with metastatic BC, the disease remains incurable, which causes at least half a million deaths related to the disease per year [ 6 11 ]. Therefore, it is important to develop novel prognostic markers associated with clinical outcomes of BC patients and to develop targeted agents that disrupt specific biological processes critical to growth of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis of data from nineteen studies showed that MRI detected additional disease in 16% of women leading to conversion from wide local excision to mastectomy in 11.3% of cases [33,39]. Multicentric breast cancer has traditionally been among the indications for mastectomy; however, BCS can also be safely performed in these patients on a condition that tumors are completely excised with negative surgical margins with acceptable cosmetic outcomes [40]. In our study, 99 patients (31.2%) had multifocal/multicentric breast cancer in total, and 62 (25.9%) patients with multifocal/multicentric BC in group 1 had a chance to save the breast by using PM + MLDF surgical technique.…”
Section: Discussionmentioning
confidence: 99%
“…This marks a significant departure from earlier guidelines where multicentric disease was considered an absolute contraindication to BCT . With this paradigm shift, it has been recognized that the use of quadrants to distinguish multifocality from multicentricity may be inappropriate as it is based on arbitrary parameters which do not take into account anatomical considerations . In contrast, the segment classification gives attention to the approximate distribution of the mammary lobes and the sick lobe hypothesis, potentially optimizing local control when the affected segment(s) is(are) excised.…”
Section: Operative Treatment Outcomesmentioning
confidence: 99%
“…4 With this paradigm shift, it has been recognized that the use of quadrants to distinguish multifocality from multicentricity may be inappropriate as it is based on arbitrary parameters which do not take into account anatomical considerations. 5 In contrast, the segment classification gives attention to the approximate distribution of the mammary lobes and the sick lobe hypothesis, 3 potentially optimizing local control when the affected segment(s) is(are) excised. It also provides a different perspective from the quadrant classification in terms of preoperative planning.…”
mentioning
confidence: 99%